Additive Effect of Coexisting Aneurysms Increases Subarachnoid Hemorrhage Risk in Patients With Multiple Aneurysms. Issue 7 (6th May 2021) - Feng, Xin; Tong, Xin; Peng, Fei; Niu, Hao; Qi, Peng; Lu, Jun; Zhao, Yang; Jin, Weitao; Wu, Zhongxue; Liu, He; Zhao, Yuanli; Liu, Aihua; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: It remains unclear whether the additive effect of coexisting intracranial aneurysms increases the risk of subarachnoid hemorrhage (SAH) in patients with multiple intracranial aneurysms. We have performed a tentative analysis for the additive effect of coexisting aneurysms. Methods: This multi-institutional cross-sectional study included 1781 aneurysms from 746 patients with multiple intracranial aneurysms. Using the generalized linear mixed model, we analyzed risk factors associated with individual aneurysm rupture and assessed the additive risk of SAH for each patient. Results: The coexisting aneurysms number was not significantly associated with individual intracranial aneurysm rupture, both in unadjusted and adjusted analyses. Patient-level analysis found that an increased number of coexisting aneurysms was significantly associated with a greater estimated additive risk ( P <0.001). Estimated additive risks of patients with 2, 3, and 4 or more coexisting intracranial aneurysms were 25.9%, 31.8%, and 38.1%, respectively, which are comparable to the actual incidence of SAH in those patients (26.6%, 29.5%, and 36.5%, respectively), with a Spearman correlation coefficient of 1.000 ( P <0.001). Compared with aneurysm-related factors, the estimated additive effect had better discrimination power for SAH risk, with areas under the receiver operating characteristic curve of 0.821. Conclusions: We found that a greater number of coexisting aneurysms did not increase rupture risk of individual aneurysms, but the potential additive effect might increase SAH risk in patients with multiple intracranial aneurysms.